2006
DOI: 10.1002/erv.770
|View full text |Cite
|
Sign up to set email alerts
|

Eating problems and personality traits. An Italian pilot study among 992 high school students

Abstract: Dieting and higher BMI are confirmed as correlates of eating problems. Personality traits measured with the TCI emerge for the first time as correlates of eating problems. Longitudinal studies should clear whether these are risk factors or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
4
12
1
Order By: Relevance
“…These data are consistent with the results of previous studies that have identified these traits as characterizing ED samples when compared to healthy controls [12]. Other studies have shown that these traits persist after recovery from the ED [50] and that they are altered in adolescents at high risk for developing a clinically significant ED [30]. Both in the acute phase and after remission, also patients with MD but without ED obtained high HA and low SD scores on the TCI [1723].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These data are consistent with the results of previous studies that have identified these traits as characterizing ED samples when compared to healthy controls [12]. Other studies have shown that these traits persist after recovery from the ED [50] and that they are altered in adolescents at high risk for developing a clinically significant ED [30]. Both in the acute phase and after remission, also patients with MD but without ED obtained high HA and low SD scores on the TCI [1723].…”
Section: Discussionsupporting
confidence: 91%
“…This association is supported by previous researches showing that individuals with purging symptomatology are more likely to show comorbid disorders and greater clinical severity [30, 31]. Also our group in previous studies found a correlation—although not related to diagnosis—with purging symptomatology [5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As far as gender differences are concerned, the higher prevalence of unhealthy eating behaviours and attitudes among women is a well-known fact [26,27,28]. Furthermore, no significant differences have been found amongst females according to the academic discipline.…”
Section: Resultsmentioning
confidence: 99%
“…Although our participants were sampled from a non-clinical population, several studies have shown that body dissatisfaction is pervasive among young women (Kenardy et al, 2001; McCabe and Ricciardelli, 2001; Abbate-Daga et al, 2007). A discrepancy between reliable others’ body perception and self- vs. metacognitive representation of one’s own body is in keeping with studies by Jansen et al (2005, 2006).…”
Section: Discussionmentioning
confidence: 99%